The Streaming Shift: Factor Driving Student Subscriptions at UiTM Kota Bharu - Haidar Ishak, Muhammad Ammar; Suhaimin, Mohd Faiez; Nik Min, Nik Mohd Faris; Abdullah Thani, Ayu Kamareenna; Maliki, Ainur Farhana; Yahaya, Nazihah Wahidah; Wan Kerana, Wan Nurhidayah (International Journal of Accounting, Finance and Business, 2025)
: The rapid evolution of the media sector, driven by technological advancements, has significantly shifted consumer preferences from traditional television to online streaming platforms. This study, which adopts a cross-sectional approach, explores the factors that influence undergraduate students' online streaming subscriptions at Universiti Teknologi MARA (UiTM) Kota Bharu. It seeks to determine significant differences in subscription patterns based on demographic factors such as gender and academic program, as well as to analyse how cost, customer service, ease of use, and social trends are related to these behaviours. A total of 293 students were randomly selected using stratified sampling, and they completed a structured questionnaire. Through multiple linear regression analysis, it was found that ease of use, cost, customer service, and social trends significantly influence students' streaming subscriptions, accounting for 65.6% of the variance in their subscription behaviours. The results indicate that streaming platforms should focus on offering user-friendly designs, competitive pricing, high-quality customer support, and alignment with current social trends in order to attract and retain student users. This research enhances the understanding of consumer behaviour in the digital age and provides useful insights for streaming providers looking to improve their market strategies. Future studies could benefit from larger sample sizes and the inclusion of additional variables to further verify these conclusions.